2022
DOI: 10.1186/s12934-022-01790-9
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS-based 13C metabolic flux analysis resolves the parallel and cyclic photomixotrophic metabolism of Synechocystis sp. PCC 6803 and selected deletion mutants including the Entner-Doudoroff and phosphoketolase pathways

Abstract: Background Cyanobacteria receive huge interest as green catalysts. While exploiting energy from sunlight, they co-utilize sugar and CO2. This photomixotrophic mode enables fast growth and high cell densities, opening perspectives for sustainable biomanufacturing. The model cyanobacterium Synechocystis sp. PCC 6803 possesses a complex architecture of glycolytic routes for glucose breakdown that are intertwined with the CO2-fixing Calvin-Benson-Bassham (CBB) cycle. To date, the contribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…The possible explanations are: i) a minor flux via ED-P, as suggested in our own flux estimation, ii) significant flux under certain conditions, such as fluctuating light ( Schulze et al, 2022 ), which may explain previously reported significant level of KDPG ( Chen et al, 2016 ), otherwise undetectable ( Will et al, 2019 ; Schulze et al, 2022 ); we note that 10% fluctuations in light (i.e., ATP and NADPH regeneration in the model) did not influence our flux estimations (data not shown) for Δ eda , or iii) ED-P is missing in Synechocystis . Furthermore, Δ eda was reported to deactivate OPP shunt ( Schulze et al, 2022 ), which disagrees with our model prediction purely based on the metabolic flux via ED-P. Thus, Δ eda mediated deactivation of OPP could support either of the presented hypotheses, i.e., role of KDPG in carbon catabolite repression or the other role of EDA in the proximity of TCA cycle might play a role in regulating OPP as neither of these scenarios are in the model.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…The possible explanations are: i) a minor flux via ED-P, as suggested in our own flux estimation, ii) significant flux under certain conditions, such as fluctuating light ( Schulze et al, 2022 ), which may explain previously reported significant level of KDPG ( Chen et al, 2016 ), otherwise undetectable ( Will et al, 2019 ; Schulze et al, 2022 ); we note that 10% fluctuations in light (i.e., ATP and NADPH regeneration in the model) did not influence our flux estimations (data not shown) for Δ eda , or iii) ED-P is missing in Synechocystis . Furthermore, Δ eda was reported to deactivate OPP shunt ( Schulze et al, 2022 ), which disagrees with our model prediction purely based on the metabolic flux via ED-P. Thus, Δ eda mediated deactivation of OPP could support either of the presented hypotheses, i.e., role of KDPG in carbon catabolite repression or the other role of EDA in the proximity of TCA cycle might play a role in regulating OPP as neither of these scenarios are in the model.…”
Section: Resultsmentioning
confidence: 73%
“…This study ( Schulze et al, 2022 ) compared WT and Δ eda , however, the authors could not detect any flux via ED-P. The possible explanations are: i) a minor flux via ED-P, as suggested in our own flux estimation, ii) significant flux under certain conditions, such as fluctuating light ( Schulze et al, 2022 ), which may explain previously reported significant level of KDPG ( Chen et al, 2016 ), otherwise undetectable ( Will et al, 2019 ; Schulze et al, 2022 ); we note that 10% fluctuations in light (i.e., ATP and NADPH regeneration in the model) did not influence our flux estimations (data not shown) for Δ eda , or iii) ED-P is missing in Synechocystis . Furthermore, Δ eda was reported to deactivate OPP shunt ( Schulze et al, 2022 ), which disagrees with our model prediction purely based on the metabolic flux via ED-P.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations